Soil resources and functional trait trade-offs determine species biomass stocks and productivity in a tropical dry forest - Caleño-Ruiz, Blanca Luz; Garzón, Fabian; López-Camacho, René; Pizano, Camila; Salinas, Viviana; González-M, Roy (Frontiers in Forests and Global Change, 2023)
Previous studies have shown that environmental conditions and plant attributes determine biomass stocks and productivity across multiple tropical forests. However, it is less clear how these factors act at local scales. We evaluated how the spatial variation of soil resource availability (soil nutrient and water content) and plant functional traits determine species biomass stocks and productivity in a Colombian tropical dry forest, based on spatially explicit soil sampling and an intensive plant trait characterization of 89 species in three 1-ha permanent plots with similar climate and floristic composition. Within each plot, we measured nine soil variables and ten functional traits and quantified forest biomass stocks and productivity for 10,161 individual trees in a period of 3 years. The soil resources where species were located and their functional traits had coordinated effects on the spatial distribution of forest biomass stocks across the plots. The highest biomass stocks were concentrated on nutrient-rich soils with low water availability and were dominated by conservative species with dense tissues and low hydraulic failure risk, probably because they are able to better cope with water limitation. Most of the remaining forest biomass stocks were found in nutrient-poor soils with high water availability and were dominated by acquisitive species. Sites with nutrient-rich soils and low water availability increased biomass survival but also mortality; however, the presence of conservative species in these sites also increased biomass survival, decreased mortality, and led to biomass accumulation, probably because their strong and hydraulically secure tissues are able to deal with water limitation for nutrient absorption during dry seasons. Interestingly, soil resources and functional traits had no effects on biomass recruitment. We conclude that strong coordinated effects of soil resources and functional traits determine local biomass processes of tropical dry forests with a central role of conservative trait species types, whereby these species promote community assembly and functioning but are also vulnerable to potential changes in water availability. Thus, conservation and restoration actions should pay special attention to soil and plant functional trait trade-offs to improve management practices in these threatened forests.